Sagot :
Answer:
w=kx/y^2
w=kx/y^218=k(8)
w=kx/y^218=k(8)(4)^2
w=kx/y^218=k(8)(4)^2k(8)= 18(16)
w=kx/y^218=k(8)(4)^2k(8)= 18(16)k(8)=288
w=kx/y^218=k(8)(4)^2k(8)= 18(16)k(8)=288k=288/8
w=kx/y^218=k(8)(4)^2k(8)= 18(16)k(8)=288k=288/8k=36
w=kx/y^218=k(8)(4)^2k(8)= 18(16)k(8)=288k=288/8k=36w=(36)(4)
w=kx/y^218=k(8)(4)^2k(8)= 18(16)k(8)=288k=288/8k=36w=(36)(4)(6)^2
w=kx/y^218=k(8)(4)^2k(8)= 18(16)k(8)=288k=288/8k=36w=(36)(4)(6)^2w= 144
w=kx/y^218=k(8)(4)^2k(8)= 18(16)k(8)=288k=288/8k=36w=(36)(4)(6)^2w= 14436
w=kx/y^218=k(8)(4)^2k(8)= 18(16)k(8)=288k=288/8k=36w=(36)(4)(6)^2w= 14436w=4
Step-by-step explanation:
Pa brainlest ^-^